PELAKSANAAN PERJANJIAN PEKERJAAN KONTRUKSI PENINGKATAN JALAN KAWASAN PERUMAHAN DAN PEMUKIMAN KELURAHAN REMBIGA MELALUI SISTEM PENUNJUKAN LANGSUNG (Studi Kasus CV. Asry Tenang Mataram) - Hani Rosdiana; Salim HS (Fakultas Hukum Universitas Mataram, 2021)
This work aims are to know implementation of work construction agreement on improvement of roads within housing and resettlement area in Rembige District, through direct appointment and also to know taken steps if one party unable to perform the contract whether because of default or force major. Type of this research is normative-empiric legal research which applies statute, conceptual and sociological approaches. the data collected by field and library researches and it analyzed descriptively-qualitatively. From research’s result, it is shows that implementation of construction work agreement through direct appointment in CV. Arsy Tenang Mataram has been follow the Art. 38 Presidential Regulation Number 16 of 2018 on Goods/Services Government Procurement